Mechanical ventilation. Part I: Physiology and pathophysiology - NIKOLAOU (Χ. ΝΙΚΟΛΑΟΥ), Ch.; SAVVAS (Ι. ΣΑΒΒΑΣ), I.; PAPASTEFANOU (Α. ΠΑΠΑΣΤΕΦΑΝΟΥ), A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Despite the fact that mechanical ventilation is an integral part of anaesthesia practice, its widespread use in veterinary medicine has yet to be established. The increasing needs and advances in animal pain management, being associated with anaesthetic protocols that can cause hypoventilation, make the use of mechanical ventilation more necessary than ever. Although mechanically ventilating the patient is not pivotal in a substantial number of surgical techniques, inability to do so precludes certain anaesthetic protocols from being used, making the choice of the drugs to be employed troubleshooting. Successful mechanical ventilation requires a thorough understanding of the physiology and pathophysiology of respiration, as well as the way mechanical ventilation affects them. Before any attempt to describe mechanical ventilation, a glossary of technical terms has to be accepted, as long as consensus between the authors has not been found in the literature. Lung elasticity, resistance to flow, inspiration time and the ratio of inspiration to expiration time interact during mechanical ventilation affecting the final result on the patient. Volutrauma, barotrauma, ventilation-perfusion mismatch and cardiac output decrease are some of the adverse effects of mechanical ventilation. The choice of whether or not to use automatic ventilators, the choice of the right equipment and setting the variables correctly on the control panel need a thorough understanding of patient pathology. This article reviews respiration under normal and pathologic conditions and the effects mechanical ventilation exerts on different organ systems. Guidelines for the application of mechanical ventilation under various pathologic conditions are provided.